Drivers and challenges of XBRL adoption process in Malaysia : experiences of four regulators in the financial reporting environment / Azleen Ilias - Ilias, Azleen (2019)
Extensible Business Reporting Language (XBRL) has evolved for over more than a decade that it affects the financial reporting landscape worldwide. However, since its evolvement, XBRL has yet to be fully adopted around the world, particularly in Malaysia. This study aims at providing better understanding on XBRL adoption by identifying the current state of XBRL adoption and type of adopter among the regulators in Malaysia. Subsequently, this study identifies what factors and how these factors influence XBRL adoption process of the regulators. This study develops a framework by utilising two research frameworks developed by Rogers's (1983) adoption process and DiPietro, Wiarda and Fleischer's (1990) Technological, Organisational and Environmental (TOE) framework. A case study approach consisting of interview and content analysis was used. This study shows that the regulators are moving towards full XBRL adoption although slow. Out of the four regulators, two regulators are considered early adopters whilst the remaining two regulators are early majority. Within the technological context, relative advantage and trialability are the driving factors in the knowledge and persuasion phase. In the decision-making phase, compatibility of XBRL taxonomy and stability production of XBRL instance documents, and standardised XBRL submission are the driving factors whilst stability of XBRL taxonomy, standardised XBRL taxonomy, availability of tools and software are challenges in the XBRL adoption process. In the implementation and confirmation phase, complexity of XBRL taxonomy is considered a challenge in the XBRL adoption process. Within the organisational context, management support is the driving factor whilst lack of expertise, skills and knowledge on XBRL are considered a challenge in the knowledge and persuasion phase. In the decision-making phase, capability and data assurance are challenges whilst in the implementation and confirmation phase, resource capacity, cost of adoption and financial resources are the driving factors to XBRL adoption process. Finally, within the environmental context, in the knowledge and persuasion phase, the driving factor is success stories. In the decisionmaking phase, the driving factors are motivation of regulatory pressure and incentive provision whilst lack of effective XBRL committee involvement, leadership of XBRL committee, work culture communication among XBRL committee members are challenges in the XBRL adoption process. In the implementation and confirmation stage, reliance on external support, lack of government support, limited trading partners, critical mass, professional bodies' pressure and stakeholders' involvement are considered challenges in the XBRL adoption process. The findings in this study serve as guidelines to other regulators that have plans to adopt XBRL.